Rancang Bangun Keran Wudhu Otomatis Berbasis Mikrokontroller di SMA Muhammadiyah 4 Songgon Banyuwangi - Pambudi, Setyo; Fikri, Azhar; Tsabit, Mumtadz Zaid Bin; Aditya, Tsabit; Karisma, Muhamat Dwi; Asrofi, Mochamad (Yayasan Inspirasi El Burhani, 2024)
Water is a primary need for worship, especially for Muslims. Making water taps automatically is one of the innovations to make water use efficient when performing ablution. This service program aims to provide education to students of SMA Muhammadiyah 4 Songgon Banyuwangi in making designs for automatic ablution faucets. The community service methods used are socialization and direct practical training in the field. Several stages in this service include simulation, assembly, programming and tool function testing. The results show that direct training related to the design of automatic ablution tap has succeeded in increasing the interest of Muhammadiyah 4 Songgon High School students in higher education. This service program must continue to be carried out continuously so that sustainability is maintained and students' interest in learning increases.